Azygos continuation of the inferior vena cava in carcinoma of oesophagus - MY, Mubarak (IIUM Medical Journal Malaysia, 2008)
The azygos system enlarges in cases of obstruction to the superior vena cava or inferior vena cava and result in increase blood flow through the system. Azygos continuation of the inferior vena cava is usually congenital and asymptomatic. The azygos vein is the sole drainage of the blood from the lower half of the body to the heart. It is crucial to identify the anomaly as it might involve in the surgical planning of tumours in the thorax or abdomen. Computed Tomography is a non-invasive technique and provide important information about the tumour and the vascular anomaly.